Resisting Structural Evil : Love as Ecological-Economic Vocation - Moe-Lobeda, Cynthia D., 1954- (Book collections on Project MUSE., 2013)
In this book the author argues that environmental threats to the earth are connected to economic equity, social values and justice, and Christian conscience.